2009
DOI: 10.3899/jrheum.090194
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 (IL-6) Deficiency Delays Lupus Nephritis in MRL-FaslprMice: The IL-6 Pathway as a New Therapeutic Target in Treatment of Autoimmune Kidney Disease in Systemic Lupus Erythematosus

Abstract: IL-6 is a strong promoter of lupus nephritis and may be a promising new therapeutic target in the treatment of human lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 53 publications
5
106
1
4
Order By: Relevance
“…To date, most of the JAK-targeting activities have been centered on rheumatoid arthritis, psoriasis, myeloproliferative diseases, and cancer (41)(42)(43)(44)(45). Targeting cytokine/growth factor pathways important for plasma cell generation and SLE development is supported by the literature, and targeting the IL-6 pathway and receptor for SLE treatment is currently being tested (13,46,47). Targeting of the BAFF pathway has been successful, and studies in the field are under way to look at the role of APRIL in plasma cell generation (48).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, most of the JAK-targeting activities have been centered on rheumatoid arthritis, psoriasis, myeloproliferative diseases, and cancer (41)(42)(43)(44)(45). Targeting cytokine/growth factor pathways important for plasma cell generation and SLE development is supported by the literature, and targeting the IL-6 pathway and receptor for SLE treatment is currently being tested (13,46,47). Targeting of the BAFF pathway has been successful, and studies in the field are under way to look at the role of APRIL in plasma cell generation (48).…”
Section: Discussionmentioning
confidence: 94%
“…Most important is the role of IL-6 as this cytokine has been implicated in multiple autoimmune diseases and directly contributes to plasma cell survival in bone marrow niches (10). In addition, multiple studies in mouse models of SLE have repeatedly demonstrated the importance of IL-6 in driving SLE disease manifestations (3,7,(11)(12)(13). Plasmablasts, precursors of plasma cells, require both APRIL and IL-6, and to a lesser degree BAFF, for full terminal differentiation to bone marrow-derived long-lived plasma cells (LL-PCs) (10,14).…”
mentioning
confidence: 99%
“…Intrinsic renal cells produce IL-6, and this can be enhanced by anti-DNA antibodies (73). In lupus-prone mice, IL-6 exacerbates GN while inhibiting IL-6 signaling attenuated GN and reducing autoimmunity, therefore enhancing survival (74). Most IL-6 inhibition trials have occurred in RA while data are emerging in SLE.…”
Section: Autoimmune Crescentic Glomerulonephritis Lupus Nephritismentioning
confidence: 99%
“…30 Much later, a study in IL-6-deficient mice confirmed these findings in the same model. 31 In a second model of SLE, three studies supported proinflammatory effects of IL-6. First, recombinant IL-6 aggravated pathogenic immune responses and the clinical course of SLE in NZW3NZB mice.…”
mentioning
confidence: 99%